2016
DOI: 10.17763/0017-8055.86.2.206
|View full text |Cite
|
Sign up to set email alerts
|

Making Through the Lens of Culture and Power: Toward Transformative Visions for Educational Equity

Abstract: In this essay, Shirin Vossoughi, Paula Hooper, and Meg Escudé advance a critique of branded, culturally normative definitions of making and caution against their uncritical adoption into the educational sphere. The authors argue that the ways making and equity are conceptualized can either restrict or expand the possibility that the growing maker movement will contribute to intellectually generative and liberatory educational experiences for working-class students and students of color. After reviewing various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
212
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(218 citation statements)
references
References 20 publications
3
212
0
3
Order By: Relevance
“…e concerns of Vossoughi et al [68] and Chachra [22] regarding Making not being equitable relate to the people aspect of the framework. ere is a need for research on how different people want or do not want to engage in educational Makerspaces.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…e concerns of Vossoughi et al [68] and Chachra [22] regarding Making not being equitable relate to the people aspect of the framework. ere is a need for research on how different people want or do not want to engage in educational Makerspaces.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…In seeking to understand the confluence of the technology tools within these contexts, we found that the production tasks, support for not knowing by adult mentors and teachers, and group norms that embraced contradictions and allowed for contestation all contributed to generative “contemporary making practices” that led toward “collective transformation” (Vossoughi, Hooper, & Escudé, , p. 227) at personal and local levels. Thus, beyond even the “collaborative purposeful transformation of the world” (Stetsenko, , p. 471), we found that the work these youths engaged in yielded collaborative cotransformations, experiences of exchange that affected participants and learning in multiple directions and often across social boundaries.…”
Section: Collaborative Cotransformationsmentioning
confidence: 99%
“…As we described earlier, the promise of making as a fundamentally democratizing movement in education is rhetorically important but practically unfulfilled. The reality of who gets to be called a maker, what forms of making are valued in popular discourse and to what end, reinscribes the straw man position of white, middle-class males as the innovators of tomorrow (Blikstein & Worsley, 2016;Vossoughi et al, 2016). Many public libraries, however, because of their physical locations in all neighborhoods regardless of socioeconomic status, their ability to offer services for free to their publics, and their efforts to solicit community feedback to maintain local relevance are well situated to challenge the status quo.…”
Section: How the Bubbler Helps Us Better Understand Multiple Construcmentioning
confidence: 99%
“…Making is often characterized by a "hacker culture" ideal dominated by white, middle-class males (Blikstein & Worsley, 2016;Brahms & Crowley, 2016a). Specifically, the contributions of women of all ages and communities of color are often devalued (Buechley, 2013;Kafai, Fields, & Searle, 2014;Vossoughi, Hooper, & Escudé, 2016). Mainstream media also perpetuates a limited view of what counts as maker activities, focusing on product over process, and valuing "innovative" products that primarily fit comfortably within a culture of affluence (Blikstein & Worsley, 2016;Sivek, 2011).…”
Section: Introductionmentioning
confidence: 99%